Post-infarction ventricular septal defect: percutaneous or surgical management in the UK national registry. (17th September 2022) - Giblett, Joel P; Matetic, Andrija; Jenkins, David; Ng, Choo Y; Venuraju, Shreenidhi; MacCarthy, Tobias; Vibhishanan, Jonathan; O'Neill, John P; Kirmani, Bilal H; Pullan, D Mark; Stables, Rod H; Andrews, Jack; et al.
Abstract: Aims: Post-infarction ventricular septal defect (PIVSD) is a mechanical complication of acute myocardial infarction (AMI) with a poor prognosis. Surgical repair is the mainstay of treatment, although percutaneous closure is increasingly undertaken. Methods and resuts: Patients treated with surgical or percutaneous repair of PIVSD (2010–2021) were identified at 16 UK centres. Case note review was undertaken. The primary outcome was long-term mortality. Patient groups were allocated based upon initial management (percutaneous or surgical). Three-hundred sixty-two patients received 416 procedures (131 percutaneous, 231 surgery). 16.1% of percutaneous patients subsequently had surgery. 7.8% of surgical patients subsequently had percutaneous treatment. Times from AMI to treatment were similar [percutaneous 9 (6–14) vs. surgical 9 (4–22) days, P = 0.18]. Surgical patients were more likely to have cardiogenic shock (62.8% vs. 51.9%, P = 0.044). Percutaneous patients were substantially older [72 (64–77) vs. 67 (61–73) years, P < 0.001] and more likely to be discussed in a heart team setting. There was no difference in long-term mortality between patients (61.1% vs. 53.7%, P = 0.17). In-hospital mortality was lower in the surgical group (55.0% vs. 44.2%, P = 0.048) with no difference in mortality after hospital discharge ( P = 0.65). Cardiogenic shock [adjusted hazard ratio (aHR) 1.97 (95% confidence interval 1.37–2.84), P < 0.001), percutaneous approach [aHR 1.44 (1.01–2.05), P = 0.042], and number of vessels with coronary artery disease [aHR 1.22 (1.01–1.47), P = 0.043] were independently associated with long-term mortality. Conclusion: Surgical and percutaneous repair are viable options for management of PIVSD. There was no difference in post-discharge long-term mortality between patients, although in-hospital mortality was lower for surgery. Structured Graphical Abstract: Structured Graphical Abstract